"Love without sex is friendship. Sex without love is desire": sex life in old age - Mirela Berger (Kairós Gerontologia, 2013)
The article deals with sexuality in old age. This is a comparative study between classes "A" and "D". The main objective of this paper is to state the following paradox: on the one hand, sexuality in old age has been affirmed and valued in the construction of feminine self-esteem, on the other, can not only blame the woman who can not adhere to them, as well as produce a new homogenization of "being old" now associated with the proper management of sexuality.